Specific fungi associated with response to capsulized fecal microbiota transplantation in patients with active ulcerative colitis - Chen, Qiongyun; Fan, Yanyun; Zhang, Bangzhou; Yan, Changsheng; Chen, Zhangran; Wang, Lin; Hu, Yiqun; Huang, Qingwen; Su, Jingling; Ren, Jianlin; Xu, Hongzhi (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: Fecal microbiota transplantation (FMT) is a novel microbial treatment for patients with ulcerative colitis (UC). In this study, we performed a clinical trial of capsulized FMT in UC patients to determine the association between the gut fungal community and capsulized FMT outcomes. Design: This study recruited patients with active UC (N = 22) and healthy individuals (donor, N = 9) according to the criteria. The patients received capsulized FMT three times a week. Patient stool samples were collected before (week 0) and after FMT follow-up visits at weeks 1, 4, and 12. Fungal communities were analysed using shotgun metagenomic sequencing. Results: According to metagenomic analysis, fungal community evenness index was greater in samples collected from patients, and the overall fungal community was clustered among the samples collected from donors. The dominant fungi in fecal samples collected from donors and patients were Ascomycota and Basidiomycota. However, capsulized FMT ameliorated microbial fungal diversity and altered fungal composition, based on metagenomic analysis of fecal samples collected before and during follow-up visits after capsulized FMT. Fungal diversity decreased in samples collected from patients who achieved remission after capsulized FMT, similar to samples collected from donors. Patients achieving remission after capsulized FMT had specific enrichment of Kazachstania naganishii, Pyricularia grisea, Lachancea thermotolerans, and Schizosaccharomyces pombe compared with patients who did not achieve remission. In addition, the relative abundance of P. grisea was higher in remission fecal samples during the follow-up visit. Meanwhile, decreased levels of pathobionts, such as Candida and Debaryomyces hansenii, were associated with remission in patients receiving capsulized FMT. Conclusion: In the metagenomic analysis of fecal samples from donors and patients with UC receiving capsulized FMT, shifts in gut fungal diversity and composition were associated with capsulized FMT and validated in patients with active UC. We also identified the specific fungi associated with the induction of remission. ClinicalTrails.gov (NCT03426683).